Combined use of traditional core logging and televiewer imaging for practical geotechnical data collection - Gwynn, X.P.; Brown, M.C.; Mohr, P.J. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Acoustic and optical televiewers are becoming routinely used to capture structural geotechnical data for use in pit slope and underground design. They provide rapid and accurate high resolution oriented images of the borehole walls and can be used as a replacement for manual core orientation techniques, with the picking of structures being left to the televiewer operator who then provide the data to the geotechnical engineers. SRK UK Ltd. has developed an approach where the raw acoustic televiewer logs are used in conjunction with manual rock mass logging of the core. This hybrid logging method allows for the detailed description of each open feature whilst making use of the accurate structural orientation measurements obtained from the televiewer data. The depth correlated structural logging data is subsequently used to populate a rock mass log, automatically producing rock mass classification values. This rapidly reduces the time required for geotechnical logging; thus reduces field time requirements of the consultant and potentially reduces cost to the client. The paper covers the current field methodology, required post processing of the logged data and discusses advantages and disadvantages of using this hybrid method. A case study from Scandinavia is also presented.